Dissolution Study on Grape Polyphenol Hard Gelatin Capsule Dietary Supplements - Lyu, Weiting; Omar, Thamer; Patel, Harna; Rodriguez, David; Ferruzzi, Mario G.; Pasinetti, Giulio M.; Murrough, James W.; Muzzio, Fernando J.; Simon, James E.; Wu, Qingli (Frontiers in Nutrition, 2021)
Methods for dissolution study with UHPLC-QqQ/MS analysis of grape polyphenol dietary supplements including grape seed extract (GSE) and resveratrol (RSV) capsules were developed following the guidance of United States Pharmacopeia (USP) <2040>. Two dissolution media, 0.1 N hydrochloric acid (pH 1.2) and 0.05 M acetate buffer (pH 4.6), were evaluated with dissolution apparatus (USP 1), 100 rpm rotation speed and 900 ml dissolution medium volume. Dissolution profiles were performed over 120 mins. The major phenolic compounds of gallic acid, catechin, epicatechin and procyanidin B2 were quantitated to obtain the dissolution profile of GSE capsules and trans-resveratrol was used for RSV capsules. Results indicated that the released trans-resveratrol for RSV capsules in both dissolution meets the USP standards, whilst for GSE capsules, all the 4 marker compounds passed the dissolution test in HCl medium but did not reach a 75% release within 60 min in acetate buffer. These promising results suggest that the general USP dissolution protocols are adequate for successful release of RSV capsules in HCl medium and acetate buffer and GSE capsules (in HCl medium), but may be inadequate for GSE capsules in acetate buffer. These results showed that under the low pH of 1.2 (simulate stomach environment), the bioactive compounds were released timely from the GSE capsules and met USP guidelines, however, under the higher pH environment of 4.6 (simulate duodenum) these same biomarkers failed, suggesting the need to further improve the dissolution of GSE over a wider range of pH environments to enhance bioavailability and efficacy.